The Influence of Using the QRIS Digital Payment Method on Customer Purchasing Decisions - Sukmardin Zalukhu; Arny Lattu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The development of digital technology has brought significant changes across various sectors, including payment systems. The Quick Response Code Indonesia Standard (QRIS) is one of the key innovations in digital payment systems developed by Bank Indonesia and the Indonesian Payment System Association. This study aims to analyze the impact of using the digital payment method QRIS on consumer purchasing decisions in Sukabumi City using the Technology Acceptance Model (TAM) approach. The variables studied include perceived usefulness, user attitude, and intention to use, measured through an online questionnaire involving 98 respondents. The results show that these three variables significantly influence purchasing decisions. QRIS is believed to provide convenience, efficiency, and comfort in transactions, thereby encouraging positive attitudes and high usage intentions. In conclusion, the implementation of QRIS can enhance transaction efficiency and positively impact consumer purchasing behavior, particularly in the MSME sector. This research contributes to the development of digital payment systems in Indonesia and is expected to provide input for policymakers in supporting broader adoption of QRIS.